2014
DOI: 10.1016/j.jalz.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Association of fish oil supplement use with preservation of brain volume and cognitive function

Abstract: Objective The aim of this study was to investigate whether the use of fish oil supplements (FOSs) is associated with concomitant reduction in cognitive decline and brain atrophy in older adults. Methods We conducted a retrospective cohort study to examine the relationship between FOS use during the Alzheimer’s Disease Neuroimaging Initiative and indicators of cognitive decline. Older adults (229 cognitively normal individuals, 397 patients with mild cognitive impairment, and 193 patients with Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…25 A very recent study observed associations between fish oil supplement use and less cognitive decline and less brain atrophy in the entire study cohort that, after stratification, remained significant in the APOE e4 noncarriers only. 26 Results from randomized placebo-controlled intervention trials are also mixed, observing positive effects of longchain n-3 fatty acids among APOE e4 carriers 27,28 or in APOE e4 noncarriers. 29 One possible explanation for the previous findings of association among APOE e4 noncarriers is the larger number of participants being APOE e4 noncarriers.…”
Section: Resultsmentioning
confidence: 99%
“…25 A very recent study observed associations between fish oil supplement use and less cognitive decline and less brain atrophy in the entire study cohort that, after stratification, remained significant in the APOE e4 noncarriers only. 26 Results from randomized placebo-controlled intervention trials are also mixed, observing positive effects of longchain n-3 fatty acids among APOE e4 carriers 27,28 or in APOE e4 noncarriers. 29 One possible explanation for the previous findings of association among APOE e4 noncarriers is the larger number of participants being APOE e4 noncarriers.…”
Section: Resultsmentioning
confidence: 99%
“…The rationale for this research has been supported by human and experimental research showing-among other facts-that these nutrients constitute more than one-third of neural membrane phospholipids, and can enhance dendritic arborization, increase the levels of brain-derived neurotrophic factor and up-regulate synaptic plasticity [29][30][31]. According to several studies using optimized voxelbased morphometry on high resolution MRI, the effect of x-3 PUFAs on cognitive performance is through preservation of brain areas involved in the intrinsic mechanisms of memory, such as the anterior cingulate cortex, the amygdala, and the hippocampus [13][14][15]. It has also been stated that the effects of x-3 PUFAs in the nervous system might be mediated by their anti-inflammatory and antithrombotic properties, due to reduction of vascular risk factors associated with cognitive decline [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies assessing a possible relationship between x-3 PUFAs intake and cognitive performance are by no means uniform [3][4][5][6][7][8][9][10][11][12][13][14][15]. Some studies have focused on the effects of oily fish intake while others have studied the effects of fish oils administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that low levels of these vitamins directly correlate with cognitive decline or brain pathology (Scott et al, 2004;Kado et al, 2005). Other studies have suggested that DHA may be helpful in patients with mild cognitive impairment (Lee et al, 2013) or normal aging (in APOE ε4-negative individuals; Daiello et al, 2015); unfortunately these studies are limited due to small sample size and being retrospective, respectively. Based on this study and other results, the Alzheimer' s Disease Cooperative Study (ADCS) conducted a prospective, randomized trial in 295 patients over 18 months to determine whether DHA can slow the progression of Alzheimer' s disease.…”
Section: B Complex Vitamins: Folic Acid B6 B12mentioning
confidence: 99%